Linux administration bootcamp (Manning Publications, 2022)
This course will help you fully understand the most important and fundamental concepts of Linux server administration. More importantly, you will be able to put those concepts to use in practical real-world situations. You'll be able to configure, maintain, and support a variety of Linux systems. You can even use the skills you learned to become a Linux System Engineer or Linux System Administrator. In this course the author has shared his favorite Linux command line tricks. These tips will make your life easier at the command line, speed up your work flow, and make you feel like a certified Linux command line Ninja! If you want to see the pages of Command Line Kung-Fu come to life, then you have to watch these videos! You will be guided step by step using a logical and systematic approach. As new concepts, commands, or jargon are encountered they are explained in plain language, making it easy for anyone to understand.